Estrogen‐Related Receptor ERRα Regulation of Human Hydroxysteroid Sulfotransferase (SULT2A1) Gene Expression in Human Caco‐2 Cells. Issue 1 (13th September 2013) - Huang, Chaoqun; Zhou, Tianyan; Chen, Yue; Sun, Teng; Zhang, Shunfen; Chen, Guangping
ABSTRACT Human hydroxysteroid sulfotransferase, SULT2A1, is important for xenobiotic detoxification and the maintenance of hydroxysteroid homeostasis. Our published report suggested that estrogen‐related receptor ERRα downregulates SULT2A1 in Hep G2 cells. The results shown in this study suggest that ERRα upregulates SULT2A1 transcription in Caco‐2 cells. The deletion analysis suggested that SULT2A1 promoter region between −65 and −44 is important for this upregulation. Our further investigation suggested that ERRα binding element, ERRE51, mediates ERRα activation of SULT2A1 promoter transcription in Caco‐2 cells. The interaction of ERRE51 with ERRα was confirmed by electrophoretic mobility shift assay and chromatin immunoprecipitation analysis. Results also suggest that the difference of constitutive androstane receptor transcription levels in Hep G2 and Caco‐2 cells at least partially contribute to the cell type dependent ERRα modulation of SULT2A1 promoter transcription. ERRα regulates human SULT2A1 transcription by competing with other nuclear receptors binding to the DNA‐promoter region.